1990
DOI: 10.1038/345542a0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of sweat glands by epidermal growth factor in murine X-linked anhidrotic ectodermal dysplasia

Abstract: Tabby (Ta), a murine X-linked mutant gene, produces a syndrome of ectodermal dysplasia including anhidrosis (absence of sweat glands). Development of sweat glands is related to that of dermal ridges (dermatoglyphics) and abnormal ridges may be associated with absence of sweat glands in the human syndrome of hypohidrotic ectodermal dysplasia (HED). We have found that dermal ridges occur in normal mice but are lacking in Ta mutants. Previously we showed that epidermal growth factor (EGF) reverses delayed eyelid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 24 publications
3
48
0
Order By: Relevance
“…A possible functional association of EDA with EGF signaling is supported by previous findings in which symptoms of the mouse mutation Tabby were cured by injections of EGF (Blecher et al 1990). The expression of EGFR was recently found to be reduced in fibroblasts of EDA patients and Tabby mice (Vargas et al 1996).…”
Section: Clues To Molecular Interactionssupporting
confidence: 68%
“…A possible functional association of EDA with EGF signaling is supported by previous findings in which symptoms of the mouse mutation Tabby were cured by injections of EGF (Blecher et al 1990). The expression of EGFR was recently found to be reduced in fibroblasts of EDA patients and Tabby mice (Vargas et al 1996).…”
Section: Clues To Molecular Interactionssupporting
confidence: 68%
“…These epidermal effects contrast those described for two other members of the EGF family, EGF and TGF-a, both of which induce marked keratinocyte proliferation but do not stimulate normal keratinocyte differentiation (38,39). In addition, both EGF and TGF-a inhibit the growth of hair follicles (40,41), while EGF stimulates the growth of sebaceous (42) and sweat glands (43). In contrast, rhNDF-a2 has no apparent effect on any dermal adnexa, both in the rabbit ear excisional wound model and after systemic administration to neonatal rats (Danilenko, D. M., and G. F. Pierce, unpublished data).…”
Section: Discussionmentioning
confidence: 38%
“…This interpretation was dramatically supported by finding both phenotypic characteristics to be reversed postnatally by treatment with high systemic doses of EGF (8), a treatment that also, remarkably, resulted in the induction of functional eccrine sweat glands (9). However, like HED, neither the pathogenesis of Ta nor the nature of the Ta gene has been determined.…”
Section: Introductionmentioning
confidence: 52%
“…The waved-2 mouse has a similar phenotype to the TGF-␣-deficient mouse and was shown recently to be caused by a mutation in the EGFR which partially inactivated its intrinsic kinase activity 5-10-fold (22). Pharmacological amounts of exogenous EGF caused a dose-dependent in vivo increase in EGFR tyrosine kinase activity (22), a response conceptually analogous to correction of the Ta phenotype with exogenous EGF (9). Another recent study has indicated that even small changes in EGFR number, such as the twofold decrease seen in RV, can cause significant phenotypic changes.…”
Section: Discussionmentioning
confidence: 99%